Proceedings of the International Conference on Science and Technology (ICST 2018) 2018
DOI: 10.2991/icst-18.2018.157
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Cadmium and Chromium Metal Polluted Soil Using Compost

Abstract: Research on remediation of chromium and cadmium metal contaminated soil using compost has been carried out. Added compost was 5%, 10%, 15%, 20% and 25% w/w. The study was conducted for 14 days and observed a decrease in the concentration of heavy metals in the soil. Measurement of heavy metal concentrations using AAS Perkin Elmer instrument. Based on the results of the analysis, the highest chromium decrease was 92.222% and the highest cadmium was 90.551% in the use of 25% compost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Compost has been shown to remediate site polluted with heavy metals via anthropogenic or agronomic practices like application of agrochemicals for enhancing the performance of cultivated crops (Lim et al, 2016). We share similar view with Rusmini et al (2018) who reported that addition of compost increased the number of soil microbes with significant reduction in heavy metals than in the soil without compost.…”
Section: Average Daily Metal Intakesupporting
confidence: 82%
“…Compost has been shown to remediate site polluted with heavy metals via anthropogenic or agronomic practices like application of agrochemicals for enhancing the performance of cultivated crops (Lim et al, 2016). We share similar view with Rusmini et al (2018) who reported that addition of compost increased the number of soil microbes with significant reduction in heavy metals than in the soil without compost.…”
Section: Average Daily Metal Intakesupporting
confidence: 82%